Cerebral organoids derived from patients with Alzheimer's disease with PSEN1/2 mutations have defective tissue patterning and altered development - Vanova, Tereza; Sedmik, Jiri; Raska, Jan; Amruz Cerna, Katerina; Taus, Petr; Pospisilova, Veronika; Nezvedová, Markéta; Fedorova, Veronika; Kadakova, Sona; Klimova, Hana; Capandova, Michaela; Orviska, Petra; et al. (Cell reports, 2023)
During the past two decades, induced pluripotent stem cells (iPSCs) have been widely used to study human neural development and disease. Especially in the field of Alzheimer's disease (AD), remarkable effort has been put into investigating molecular mechanisms behind this disease. Then, with the advent of 3D neuronal cultures and cerebral organoids (COs), several studies have demonstrated that this model can adequately mimic familial and sporadic AD. Therefore, we created an AD-CO model using iPSCs derived from patients with familial AD forms and explored early events and the progression of AD pathogenesis. Our study demonstrated that COs derived from three AD-iPSC lines with PSEN1(A246E) or PSEN2(N141I) mutations developed the AD-specific markers in vitro, yet they also uncover tissue patterning defects and altered development. These findings are complemented by single-cell sequencing data confirming this observation and uncovering that neurons in AD-COs likely differentiate prematurely.
Keywords: mutace; Alzheimerova nemoc; presenilin-1; Organoids; Neurons; lidé; indukované pluripotentní kmenové buňky; Mutation; Induced Pluripotent Stem Cells; organoidy; neurony; Alzheimer Disease; Presenilin-1; Humans